Constraints and Strategies for Inclusive Education in Indonesia at the Primary School Level: A Literature Review - Humayra' Nafisah Mar'atul Latif; Pramesti Pradna Paramita (IJIP : Indonesian Journal of Islamic Psychology, 2023)
Inclusive education in Indonesia is designed for all learners, both "regular" learners and learners with special needs. Inclusive education also aims to facilitate students with special needs to be able to get along with peers in general by placing one educational environment together with "regular" students, so that it is expected to realize an educational environment that respects diversity and without discrimination. However, in its implementation there are obstacles that are not easy to face, both for inclusive schools and teachers who teach. The purpose of this research is to find out the obstacles faced by inclusive schools and teachers at the primary school level and also provide strategies that can be used to optimize inclusive education. The research method used is a qualitative method with a literature review approach. The results of the study show that some of the obstacles faced are the lack of special mentor teachers, the lack of teacher knowledge about students with special needs, the imposed curriculum, the school environment that is still not friendly for students with special needs, and so on. Teachers can use various models, strategies, media and learning resources that are tailored to the class. One strategy that schools can do is to bring in professionals to provide insight for all school members regarding students with special needs. One method or strategy that parents of children with special needs can do is to apply the TEACCH method. And for the government, the education office needs to coordinate internally, especially in the field of educators who can understand the concept and implementation of inclusion policies on an ongoing basis.